2001
DOI: 10.1038/sj.onc.1204471
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the potential suppressor gene IGFBP-rP1 in human breast cancer is associated with inactivation of the retinoblastoma protein, cyclin E overexpression and increased proliferation in estrogen receptor negative tumors

Abstract: The complex insulin-like growth factor network of ligands, receptors and binding proteins has been shown to be disturbed in breast cancer. In addition to defects in proteins controling cell cycle checkpoints, this type of aberrations could a ect tumor growth and survival thereby in¯uencing both tumor aggressiveness and potential response to treatments. We have previously identi®ed the T1A12/mac25 protein, which is identical to the IGFBP-rP1, as a di erentially expressed gene product in breast cancer cells comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 24 publications
(30 reference statements)
4
68
3
Order By: Relevance
“…TMA technology allowed for a rapid and simultaneous analysis of RNF11 protein expression in 125 primary tumours microarrayed in duplicate by immunohistochemical staining using anti-RNF11 antibody (Kononen et al, 1998;Landberg et al, 2001). Comparison of RNF11 expression between breast, prostate, head and neck, kidney, colon and lung cancers revealed that the majority of our tumour array specimens produced clear immunostaining without any detectable background, and the morphology of the tissues was well preserved (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…TMA technology allowed for a rapid and simultaneous analysis of RNF11 protein expression in 125 primary tumours microarrayed in duplicate by immunohistochemical staining using anti-RNF11 antibody (Kononen et al, 1998;Landberg et al, 2001). Comparison of RNF11 expression between breast, prostate, head and neck, kidney, colon and lung cancers revealed that the majority of our tumour array specimens produced clear immunostaining without any detectable background, and the morphology of the tissues was well preserved (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
“…Comparison of RNF11 expression between breast, prostate, head and neck, kidney, colon and lung cancers revealed that the majority of our tumour array specimens produced clear immunostaining without any detectable background, and the morphology of the tissues was well preserved (Figure 1). To facilitate comparison of our results with published data, we employed the commonly used semiquantitative evaluation of protein expression based on distinct differences between strong, moderate and lack of staining in tumour specimens developed with immunoperoxidase methods (Kononen et al, 1998;Landberg et al, 2001). RNF11 was markedly overexpressed in breast and to a somewhat lesser extent in pancreatic as well as colon cancer samples, whereas it was only weakly expressed in prostate and renal cell carcinomas (Table 1, Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, IGFBP7 (IGFBP-rP1, MAC25) binds to insulin and insulinlike growth factor 1, thereby inhibiting proliferation (Oh et al, 1996;Yamanaka et al, 1997). Interestingly, IGFBP7 expression is downregulated in several types of cancer, and restoration of its expression induces cellular senescence or apoptosis (Swisshelm et al, 1995;Lopez-Bermejo et al, 2000;Landberg et al, 2001;Mutaguchi et al, 2003). The transmembrane protein MS4A3 (HTm4) inhibits G1-S cell cycle transition in haematopoietic cells by binding to cyclin-dependent kinase (CDK)-associated phosphatase-CDK2 complexes (Donato et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The microarray analysis identified that insulin-like growth factor (IGF)-binding protein 7 (IGFBP7), which has been reported to have a tumour-suppressive activity through the induction of apoptosis in some cancers, was a key gene related to the response to this therapy (Burger et al, 1998;Landberg et al, 2001;Mutaguchi et al, 2003;Sato et al, 2007;Lin et al, 2008;Wajapeyee et al, 2008). Furthermore, we confirmed that IGFBP7 significantly correlated with the response to IFN-a/5-FU therapy in genetic manipulation experiments and to the clinical response in HCC tissue samples.…”
mentioning
confidence: 99%